The Influence of Tax Avoidance, Liquidity, Profitability, on Capital Structure in Various Industrial Sub-Sector Companies Listed on the Indonesia Stock Exchange for the Period 2021 - 2023 - Putri, Ayu Nadia; Dwiarti, Rina (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to analyze the effect of Tax Avoidance, Liquidity, Profitability, on Capital Structure in Various Industrial Sub-Sector Companies for the period 2021 - 2023. The population in this study are all Miscellaneous Industry Sub-Sector Companies listed on the Indonesia Stock Exchange in 2020 - 2023. The use of samples in this study using Purposive Sampling. There are 24 companies that meet the sample selection criteria. The analysis techniques used are Classical Assumption Test and Multiple Linear Regression Analysis. The results of this study indicate that (1) Tax Avoidance has no effect on Capital Structure, (2) Liquidity has a significant negative effect on Capital Structure, (3) Profitability has no effect on Capital Structure, (4) Tax Avoidance, Liquidity, Profitability together have a significant effect on Capital Structure.